Peran Adversity Quotient sebagai Faktor Protektif terhadap Stres Akademik pada Mahasiswa Kedokteran - Ridho Ade Nugroho (Jurnal Skala Kesehatan, 2026)
Medical students encounter high academic pressure, including workload and clinical examinations such as OSCE, which may lead to stress and impair psychological well-being. Adversity Quotient (AQ) is defined as an individual’s ability to endure and adapt to difficulties, serving as a hypothesized protective factor against stress. This study aimed to analyze the effect of Adversity Quotient on stress levels among medical students at the Faculty of Medicine, Universitas Muhammadiyah Malang. An observational analytic study with a cross-sectional design was conducted on 70 students. Data were collected using Stoltz’s AQ questionnaire and the Perceived Stress Scale-10 (PSS-10), then analyzed using Chi-Square tests and binary logistic regression. The analysis showed that age ($p = 0.488$) and gender ($p = 0.843$) were not significantly associated with stress levels. However, Adversity Quotient showed a significant association with stress ($p = 0.002$). Students with low AQ had a 5.062 times higher risk of experiencing stress compared to those with high AQ ($OR = 5.062$). Adversity Quotient has a significant effect on stress levels and functions as a primary protective factor for medical students in managing academic challenges.